Antioxidant Activity of n-hexane and Etil Acetate Fractions of Bangkal (Nauclea subdita (Korth.) Steud.) Leaves - Arnida Arnida; Al Madani; Sutomo Sutomo (Borneo Journal of Pharmacy, 2023)
Bangkal (Nauclea subdita (Korth.) Steud.) is a tropical plant belonging to the Rubiaceae family, commonly found in South Kalimantan. This plant is one of the plants that has efficacy as a medicinal plant. This study aimed to quantitatively identify secondary metabolites and antioxidant activity in the n-hexane and ethyl acetate fractions of N. subdita leaves. The method of identification of secondary metabolites using the test tube. Antioxidant activity using the DPPH method based on IC50 value. The results of identifying secondary metabolites in the n-hexane fraction of N. subdita leaves contain alkaloids, flavonoids, steroids, and phenolic compounds, while the ethyl acetate fraction of N. subdita leaves contain alkaloids, flavonoids, steroids, tannins, saponins, and phenolics. The results of the antioxidant activity test of the n-hexane fraction and the ethyl acetate fraction of the leaves of N. subdita showed IC50 values ​​of 229.61178±3.65919 and 54.54296±0.02236 ppm, respectively. Based on the IC50 value, the n-hexane fraction of N. subdita leaves had weak antioxidant activity, and the ethyl acetate fraction of N. subdita leaves had strong antioxidant activity.